2017
DOI: 10.1186/s13071-017-2579-5
|View full text |Cite
|
Sign up to set email alerts
|

Reptile-associated Borrelia species in the goanna tick (Bothriocroton undatum) from Sydney, Australia

Abstract: BackgroundKnowledge on the capacity of Australian ticks to carry Borrelia species is currently limited or missing. To evaluate the potential of ticks to carry bacterial pathogens and their DNA, it is imperative to have a robust workflow that maximises recovery of bacterial DNA within ticks in order to enable accurate identification. By exploiting the bilateral anatomical symmetry of ticks, we were able to directly compare two DNA extraction methods for 16S rRNA gene diversity profiling and pathogen detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 49 publications
4
48
0
2
Order By: Relevance
“…In the present study, bacterial profiling of I. tasmani included ticks from three states (NSW, QLD, TAS) and seven host species. With this in mind, we suggest that future studies should combine careful taxonomic status identity with data on microbial communities of I. study are in line with previous research overseas (Zhang et al, 2014;Kurilshikov et al, 2015;Sperling et al, 2017) and in Australia (Gofton et al, 2015b;Panetta et al, 2017). Molecular tools continue to develop at a rapid rate with an increasing shift towards whole-genome or shotgun sequencing (sequencing the full range of nucleic acids present in a metagenomic sample).…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, bacterial profiling of I. tasmani included ticks from three states (NSW, QLD, TAS) and seven host species. With this in mind, we suggest that future studies should combine careful taxonomic status identity with data on microbial communities of I. study are in line with previous research overseas (Zhang et al, 2014;Kurilshikov et al, 2015;Sperling et al, 2017) and in Australia (Gofton et al, 2015b;Panetta et al, 2017). Molecular tools continue to develop at a rapid rate with an increasing shift towards whole-genome or shotgun sequencing (sequencing the full range of nucleic acids present in a metagenomic sample).…”
Section: Discussionsupporting
confidence: 73%
“…The similarity of sequence of 16S rDNA from isolates was 98% to 99% when compared with Borrelia spp. isolated from Bothriocroton undatum (MG004679 or MG004684 in Figure ) ticks that were collected from wild lace lizard ( Varanus varius ) in Australia . Phylogenetic analysis based on 16S rDNA and flaB demonstrated that isolates in this study formed a monophyletic group and belonged to REP borreliae (Figures and S2).…”
mentioning
confidence: 70%
“…Bothriocroton undatum (MG004679 or MG004684 in Figure 2) ticks that were collected from wild lace lizard (Varanus varius) in Australia. 6 Phylogenetic analysis based on 16S rDNA and flaB demonstrated that isolates in this study formed a monophyletic group and belonged to REP borreliae (Figures 2 and S2). This is the first study to isolate and perform molecular characterization of a novel species of REP borreliae from Am.…”
mentioning
confidence: 73%
See 2 more Smart Citations